Your lords, not mine: Buddhist–Christian encounter and the language of directive in the ‘Kitchanukit’ - Bhasrvarin Iamsa-ard; Thanapas Dejpawuttikul; Kosit Tiptiempong (Cogent Arts & Humanities)
This article revisits the interpretation of the most crucial text in the history of scientific knowledge in Thai society: Nangsue Sadaeng Kitchanukit (A Book Explaining Various Things, 1867). Dominated by Thai historians for over four decades, the ‘Kitchanukit’, authored by Chaophraya Thiphakorawong, has been fundamentally explained not only as an early phase of Siamese elites’ reaction to Western challenges by portraying the encounter between Theravada Buddhist and Christian missionaries, but also the advent of science communication in the country. To redirect the readers’ consideration of the linguistic aspect of the text, the researchers argue that, through the method of critical discourse analysis, especially focusing on the style of speech act and conceptual metaphor in ‘Kitchanukit’, readers can gain a better understanding of Thiphakorawong’s language strategy which the researchers refer to as double demarcation. Significantly, it was employed by the author as a persuasive and hedging tactic in the Buddhist–Christian dialogue on the issue of faith and knowledge.